Old Borders and New Horizons in Multimodality Imaging of Malignant Pleural Mesothelioma - Martini, Katharina; Frauenfelder, Thomas (The Thoracic and Cardiovascular Surgeon, 2021)
Background The purpose of this article is to describe the various imaging techniques involved in detection, staging, and preoperative planning in malignant pleural mesothelioma (MPM) focusing on new imaging modalities.Methods For this purpose, first a brief summary of the etiology of MPM is given. Second, not only the commonly known, but also novel imaging modalities used in MPM will be discussed.Results A wide range of imaging methods, from conventional chest radiography, through computed tomography and hybrid imaging to radiomics and artificial intelligence, can be used to evaluate MPM.Conclusion Nowadays multimodality imaging is considered the cornerstone in MPM diagnosis and staging.
Keywords: imaging; mesothelioma; pleural disease; tumor